Evaluating the use of e-portfolio as an alternative assessment tool for students majoring Arabic and Islamic studies: some experiences from International Islamic University Malaysia - Md Ghalib, Mohd. Feham; Yahaya, Mohd. Firdaus (2011)
In line with the development of technology these days, evaluating student’s knowledge and performance at higher learning institution is not only based on the summative approach. It is rather formative approach in nature where the evaluation process is carried out consistently from the beginning of the academic semester until the end of the learning session for that current semester. One of the evolving tools to be used in this respect is an electronic portfolio (e-portfolio). The existence of this medium has opened a different dimension to the educators in evaluating and assessing students in a more appropriate and meaningful manner reflecting their intellectual development as well as learning experiences they have undergone. Additionally, e-portfolio can serve as a mediator for peer evaluation. Here, the students’ works can be reviewed later rated by their peers including classmates and the instructor alike. Features of the current e-portfolio system such as, rating the artifacts, sharing of learning materials, and communicating via internal messaging tool are only a few out of many others which can benefit it users.Taking this into account, this paper will discuss some issues as stated above pertaining to the use of e-portfolio for educational purposes as an alternative evaluation and assessment toolin particular at higher learning institution level. A field work in investigating the satisfaction of using the electronic portfolio will also be conducted to justify it use among the students. Thus, the teaching and learning process is currently not dependable on the instructors alone. It is rather a mutual communication between the instructor and his student as well as the student and his peers.